Respuesta :

Answer:

The answer is A (-3,4,6).

Step-by-step explanation:

1 Solve for z in -3x-4y+z=-1


z=3x-1+4y



2 Substitute z=3x-1+4y into 2x+y-z=-8


-x-3y+1=-8



3 Substitute z=3x-1+4y into x+8y-z=23


-2x+4y+1=23


4 Solve for x in -x-3y+1=-8


x=-3y+9



5 Substitute x=-3y+9 into z=3x-1+4y


z=-5y+26



6 Substitute x=-3y+9 into -2x+4y+1=23


10y-17=23



7 Solve for y in 10y-17=23


y=4



8 Substitute y=4 into z=-5y+26


z=6



9 Substitute y=4 into x=-3y+9


x=-3



10 Therefore,


x=-3


y=4

z=6